Implementasi Konseling Individual Teknik Behaviour Contract untuk Mengatasi Perilaku Membolos Siswa di SMAN 3 Lubuk Basung (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
This research is motivated by the high number of truancy cases at SMAN 3 Lubuk Basung, which negatively impacts student achievement and discipline. The purpose of this study is to describe the process and effectiveness of individual counseling using the behavior contract technique in addressing truancy. This study used a qualitative approach with data collection techniques through interviews, observations, and documentation of guidance and counseling teachers and students with a history of truancy. The results showed that the implementation of behavior contracts was able to increase students' awareness, responsibility, and motivation in participating in learning activities. Written agreements between counselors and clients were proven effective in fostering student commitment to changing negative behaviors into positive ones. Despite obstacles such as time constraints and variations in student responses, this technique remains effective as a guidance and counseling service strategy to reduce truancy behavior in schools.